POSSIBILIDADES DO ENSINO DA LÍNGUA ESPANHOLA NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL: UMA PROPOSTA DE FORMAÇÃO DOCENTE - Jaramillo, Marta de Las Mercedes Contardo (2010)
The present paper comes up from a project carried out in the Official Educational System of the municipality of Santo André (SP), from August to December, 2008, with teachers enrolled in a course entitled Formação sobre culturas de língua espanhola e suas possibilidades no trabalho pedagógico (Training on Spanish-language cultures and its possibilities in the pedagogical work). The most important aspect of the project was to insert teachers of the lower grades in the Spanish and Hispanic-American language and culture, directing them to obtain a globalized vision of the new existing tendencies in the acquisition of a second language. In doing so, this course enabled students-teachers to share experiences and to deepen their studies in the cultural and linguistic integration by means of facilitation methodologies and techniques adequate to the students age group, children ranging from 6 to 10 years old. From this project, the research realized looked for theorists to structure this paper which the initial question is possibilities to introduce the teaching of a foreign language in this case, Spanish in the yearly years of primary school. As there are not many teachers in Brazil who are qualified in teaching Spanish language, we asked ourselves about such possibility, considering that Municipal schools, which are the ones that offer Primary teaching, do not include a foreign language in their curriculums. Based on Theoretical that show us different ways to learn a foreign language and in front of what was shown, the study seeks to analyze statements and observations collected in the execution of individual projects that the teachers realized during the course. By the analysis of the questionnaire, interview and declaration conducted with eleven teachers of the Municipal System involved in the project, we traced their graduation profile, performance and professional trajectory. The data collected were analyzed having Jacotot and his ignorant schoolmaster of Jacques Rancière as the theoretical referential; considering Jacotot s concepts of explanation, equality and will; and submitted to content analysis. In this context, were extracted reflections of possibilities in the teachers experience during the execution of the project. The study considered after this experience that exist the possibility of teaching a continuing education of Spanish language to children for teachers who already act as teachers of the early years.(AU)